PALEOMAGNETIC VECTORS AND TILTED DIKES - Borradaile G.J. (My University, 2001)
Where tectonic deformation reorients rocks without penetrative strain, their paleomagnetic vectors may be restored to their original attitudes by untilting. For strata, paleomagnetic inclination is readily restored but the tilt axis must be precisely known if paleodeclination is required. For dikes, without the knowledge of the rotation(s), neither declination nor inclination of the paleomagnetic vector can be uniquely defined. Furthermore, back-rotating dike orientations to an upright attitude assumes primary verticality whereas primary dike dips are bimodal across the spreading axes (e.g. Troodos ophiolite, Cyprus). In the Cyprus ophiolite, the dikes of the Limassol Forest Transform Zone are tilted due to uplift of the mantle-sequence rocks and deflected against the Arakapas Fault. Their paleomagnetic vectors may be restored rotating about the two axes defined by the strike and the vertical, or about a net axis that is possibly the actual tectonic rotation axis. This net axis is determined from the tectonic regional dispersion of the dike orientations. In this test case, the results of the restorations differ slightly but underline the difficulty in selecting the best restoration procedure and the greater difficulty of restoring the paleomagnetic data from dikes vis a vis strata. For dikes, it is recommended that the paleomagnetic vectors are restored using average dike orientations to minimize the inaccuracies due to the large primary variation in dike orientation.
Keywords: UNTILTING; DIKE; PALEOMAGNETIC RESTORATION; TECTONIC RESTORATION